Pooh's Heffalump movie. - Disney, Walt; Walt Disney Enterprises (New York : Scholastic, Incorporated, 2005)
Little Roo tries to find the much-feared heffalump and ends up learning a lesson about friendship.
Keywords: Fear -- Juvenile fiction; Friendship -- Juvenile fiction; Animals -- Juvenile fiction; Winnie-the-Pooh (Fictitious character) -- Juvenile fiction